问题 解答题
怎样简便就怎样计算.
11
9
-(
2
9
+
7
13
)    
91-10÷0.25÷4
5
7
×
9
11
+
2
11
÷
7
5
35÷[
7
8
×(1-
2
7
)]
41×101
1
3
×
2
5
×
3
10
8.5-(5.6+4.8)÷1.312×(
1
4
-
1
3
+
1
6
答案

(1)

11
9
-(
2
9
+
7
13
),

=

11
9
-
2
9
-
7
13

=1-

7
13

=

6
13

(2)91-10÷0.25÷4,

=91-10÷(0.25×4),

=91-10÷1,

=91-10,

=81;

(3)

5
7
×
9
11
+
2
11
÷
7
5

=

5
7
×
9
11
+
2
11
×
5
7

=(

9
11
+
2
11
)×
5
7

=1×

5
7

=

5
7

(4)35÷[

7
8
×(1-
2
7
)],

=35÷[

7
8
×
5
7
],

=35÷

5
8

=56;

(5)41×101,

=41×(100+1),

=41×100+41,

=4100+41,

=4141;

(6)5×

1
3
×
2
5
×
3
10

=(5×

2
5
)×(
1
3
×
3
10
),

=2×

1
10

=

1
5

(7)8.5-(5.6+4.8)÷1.3,

=8.5-10.4÷1.3,

=8.5-8,

=0.5;

(8)12×(

1
4
-
1
3
+
1
6
),

=12×

1
4
-12×
1
3
+12×
1
6

=3-4+2,

=1.

单项选择题
单项选择题